Pengaruh Pemahaman Perpajakan Tentang Tarif Pajak, Sanksi Pajak, dan Keadilan Pajak terhadap Presepsi Mahasiswa Mengenai Penggelapan Pajak (Tax Evasion) - Anggita Cahyaningtyas Putri Pramesty; Juli Ratnawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study is to understand the effect of understanding tax rates, tax sanctions as well as partial tax justice on student perceptions of tax evasion. This study applies the slovin calculation of 183 respondents. The research analysis system used is multiple linear regression analysis. The results of this study are that understanding tax rates partially has a positive and significant impact on students' perceptions of tax evasion, tax sanctions partially have a negative and insignificant impact on students' perceptions of tax evasion, and tax justice partially has a positive and significant impact on students' perceptions of tax evasion. tax evasion, and tax justice simultaneously have a positive and significant impact on student perceptions of tax evasion, and tax sanctions simultaneously have no positive and insignificant impact on student perceptions of tax evasion.